The Role of Digital Government Innovation in Driving Bureaucratic Reform and Improving Sustainable Public Service Governance - Muhammad Zikri; Eko Prasojo (Ilomata International Journal of Social Science, 2026)
This paper explores how digital government innovation drives bureaucratic reform and enhances sustainable public service governance. As digital technologies evolve rapidly, governments are adopting new tools to enhance efficiency, transparency, and citizen engagement. However, the impact of these innovations on bureaucratic structures and governance remains underexplored. This study addresses the question: How do digital government innovations contribute to bureaucratic reform and sustainable governance? The novelty of this research lies in its comprehensive synthesis of existing literature, offering a unique perspective on the collective impact of digital government initiatives. While the manuscript provides a valuable integrative analysis, its novelty is focused more on synthesizing existing insights than offering new theoretical contributions. It is recommended that the study further develop an original conceptual framework to enhance its theoretical generativity. While previous studies have focused on specific aspects of digital governance, this paper provides a comprehensive view of how these innovations transform public service delivery and governance structures. Based on a qualitative approach, the study reviews 40 articles published between 2015 and 2025, focusing on themes such as efficiency, transparency, citizen participation, and sustainability. The findings indicate that digital innovations improve bureaucratic efficiency, increase transparency, and enhance citizen engagement. However, challenges like the digital divide and cybersecurity concerns still impede their full potential. In conclusion, this research emphasizes the need for investments in digital infrastructure and policies that promote digital literacy and government support to optimize the benefits of digital government innovations.